Profit from your forecasting software : a best practice guide for sales forecasters - Goodwin, Paul (Wiley & SAS business series, 2018)
With a focus on choice, interpretation, and judgement, this practical book goes beyond the technical manuals to help you truly grasp the more intangible skills of forecasting that lead to better accuracy. --